P012: Québec emergency physicians propose priority solutions to improve rural emergency care. (15th May 2017) - Audet, J.; Lapointe, L.; Renaud, M.; Turgeon-Pelchat, C.; Mathieu, B.; Fleet, R.
Abstract : Introduction: In the province of Québec, roughly 20% of the population lives in rural areas. Rural emergency departments (EDs) face different challenges than their urban counterparts. Yet, few studies have sought to understand these challenges. This study aims to survey Québec's emergency physicians to: 1) identify problems specific to rural EDs, 2) find solutions for improving accessibility and quality of care offered in rural regions and, 3) rank solutions in order of priority. These results will allow data triangulation with other of our studies that seek to identify challenges faced by rural EDs and potential solutions.Methods: During the 2016 annual conference of the Québec Emergency Physicians' Association, we asked physicians and residents (including those from urban EDs), to complete a survey about the challenges faced by rural EDs. The survey contained two sections. The first took the form of open-ended questions in which respondents could write three challenges about accessibility and quality of care in rural EDs (objective 1) and three solutions to address these challenges (objective 2). The second section listed 11 potential solutions identified in our previous study. The solutions were ranked based on their priority level on a five-point Likert scale that ranged from "not a priority" to "an absolute priority" (objective 3). We added the total number of points for each solution and produced a ranking list.Results: Ninety-one physicians out of the 417 at the conference completed the survey; 58% came from urban EDs and 42% from rural EDs. Open-ended questions suggest that access to specialists and interfacility transfers are the principal challenges faced by rural EDs. The top five solutions identified as the highest priorities were: 1) care protocols, 2) improvement of interfacility transfers, 3) training with simulators, 4) targeted ultrasound and, 5) implementation of staff retention and recruitment strategies.Conclusion: This study is relevant and useful as roughly a quarter of attendants at the conference spontaneously volunteered to help identify and prioritize solutions to foster the accessibility and quality of care in rural EDs. Furthermore, it represents a stepping stone for our recently-launched wide-scope study, Urgences Rurales 360, that aims to explore problems faced by every of the 28 rural EDs in Québec and the solutions that could be implemented to resolve them.